2022
DOI: 10.1126/sciimmunol.abp9553
|View full text |Cite
|
Sign up to set email alerts
|

Secondary infections rejuvenate the intestinal CD103 + tissue-resident memory T cell pool

Abstract: Resident T lymphocytes (T RM ) protect tissues during pathogen reexposure. Although T RM phenotype and restricted migratory pattern are established, we have a limited understanding of their response kinetics, stability, and turnover during reinfections. Such characterizations have been restricted by the absence of in vivo fate-mapping systems. We generated two mouse models, one to stably mark CD103 + T cells (a marker of T RM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 87 publications
1
20
0
Order By: Relevance
“…and Fung et al. showed that CD103 + T RM cells have limited proliferation capacity, but CD103 - T RM cells undergo robust expansion upon Ag re-encounter, further highlighting the heterogeneity within T RM pool ( 121 , 122 ). Nonetheless, successive Ag exposures improve the longevity and protective function of T RM pool; for example, 4° influenza-specific T RM cells show enhanced durability and heterosubtypic immunity than 1° T RM cells ( 123 ).…”
Section: Evolution Of the T Mem Pool After Multipl...mentioning
confidence: 99%
“…and Fung et al. showed that CD103 + T RM cells have limited proliferation capacity, but CD103 - T RM cells undergo robust expansion upon Ag re-encounter, further highlighting the heterogeneity within T RM pool ( 121 , 122 ). Nonetheless, successive Ag exposures improve the longevity and protective function of T RM pool; for example, 4° influenza-specific T RM cells show enhanced durability and heterosubtypic immunity than 1° T RM cells ( 123 ).…”
Section: Evolution Of the T Mem Pool After Multipl...mentioning
confidence: 99%
“…A set of recent mouse model studies used elegant fate-mapping approaches to assess how intestinal T RM respond to TCR-mediated reactivation. 84,85 These CD8 T-cell-focused studies found that CD103+ T RM cells had fairly limited responses to TCRmediated reactivation. We hypothesize that a similar level of T RM hyporesponsiveness may exist in the FRT, helping to maintain T RM homeostasis during inflammatory episodes.…”
Section: Maintaining Homeos Ta S Is -The T R M Compartment In Infl Am...mentioning
confidence: 99%
“…Of note, this baseline level of inflammation appears to be critical for maintenance of barrier immunity (“inflammatory surveillance”). A set of recent mouse model studies used elegant fate‐mapping approaches to assess how intestinal T RM respond to TCR‐mediated reactivation 84,85 . These CD8 T‐cell‐focused studies found that CD103+ T RM cells had fairly limited responses to TCR‐mediated reactivation.…”
Section: Maintaining Homeostasis—the Trm Compartment In Inflamed Tissuesmentioning
confidence: 99%
“…For instance, in the intestine, CD103 + CD69 + CD8 + Trm cells possess high ability to produce inflammatory cytokines, while CD103 - CD69 + CD8 + Trm cells have a high expression of β2-integrin and are more able to produce granzyme ( 28 ). Besides, researchers have found that CD103 - Trm can differentiate into CD103 + Trm to mediate immune response towards secondary infections, instead of the primarily resident CD103 + Trm ( 29 , 30 ). Besides the different function, various subsets of Trm cells, including CD103 + CD69 + , CD103 - CD69 + and CD103 - CD69 - Trm cells, have shown great potential to proliferate.…”
Section: Overview Of Tissue-resident Memory T Cellsmentioning
confidence: 99%